Analysis of Using e-Filing with The Implementation of Theory of Planned Behavior - Ita Salsalina Lingga; Endah Purnama Sari Eddy; Nunik Lestari Dewi; Clairine Agelica Riona Saputra (KINERJA, 2021)
AbstractThis study aims to examine the impact of taxpayer’s intention toward using e-filing on actual e-filing usage. This research model based on theory of planned behavior that analyze behavioral attitude, subjective norm and perceived behavioral control as factors that affect taxpayer’s intention toward using e-filling and its impact on actual e-filling usage. Analysis of data uses Partial Least Square of Structural Equation Modeling (PLS SEM). Unit of analysis in this research are accounting lecturers from several universities in Indonesia. A total of 211 lecturers as an individual taxpayer responded to the survey using questionnaires. The result findings prove that attitude toward using e-filing, subjective norm, and perceived behavioral control significantly influence taxpayer’s intention to use e-filing and in the end it will give an impact on actual e-filing usage. Keywords  theory of planned behavior, intention toward using e-filing, subjective norm, perceived behavioral control, actual e-filing usage.